Metabolic reprogramming associated with aggressiveness occurs in the G-CIMP-high molecular subtypes of IDH1mut lower grade gliomas. Issue 4 (30th October 2019) - Ruiz-Rodado, Victor; Malta, Tathiane M; Seki, Tomohiro; Lita, Adrian; Dowdy, Tyrone; Celiku, Orieta; Cavazos-Saldana, Alejandra; Li, Aiguo; Liu, Yang; Han, Sue; Zhang, Wei; Song, Hua; et al.
Abstract: Background: Early detection of increased aggressiveness of brain tumors is a major challenge in the field of neuro-oncology because of the inability of traditional imaging to uncover it. Isocitrate dehydrogenase (IDH)-mutant gliomas represent an ideal model system to study the molecular mechanisms associated with tumorigenicity because they appear indolent and non-glycolytic initially, but eventually a subset progresses toward secondary glioblastoma with a Warburg-like phenotype. The mechanisms and molecular features associated with this transformation are poorly understood. Methods: We employed model systems for IDH1 mutant (IDH1 mut ) gliomas with different growth and proliferation rates in vivo and in vitro. We described the metabolome, transcriptome, and epigenome of these models in order to understand the link between their metabolism and the tumor biology. To verify whether this metabolic reprogramming occurs in the clinic, we analyzed data from The Cancer Genome Atlas. Results: We reveal that the aggressive glioma models have lost DNA methylation in the promoters of glycolytic enzymes, especially lactate dehydrogenase A ( LDHA), and have increased mRNA and metabolite levels compared with the indolent model. We find that the acquisition of the high glycolytic phenotype occurs at the glioma cytosine-phosphate-guanine island methylator phenotype (G-CIMP)-high molecular subtype in patients and is associated with the worst outcome. Conclusion: We propose very early monitoring of lactate levels as a biomarker of metabolic reprogramming and tumor aggressiveness.